(untitled) (International Journal of Animal Biodiversity, Conservation and Systematics ( IJABC), 2025)
Landscape genetics – the integration of population genetics with landscape ecology to identify how landscape features shape gene flow and population structure – has become a cornerstone of conservation planning for large mammals in fragmented landscapes. This study presents a comprehensive landscape genetics analysis of eight large mammal species across 24 European and African landscapes, using whole-genome low-coverage sequencing (2-4x) of 4,847 individuals genotyped at 847,000 SNPs to characterise patterns of population structure, isolation-by-resistance, and genetic connectivity across contrasting landscape configurations. All eight species showed significant isolation-by-resistance (IBR) – genetic differentiation increasing with landscape resistance – with resistance surfaces derived from species-specific habitat suitability models significantly outperforming Euclidean distance models in explaining genetic structure (mean Mantel r improvement: +0.28 +- 0.06). Highway networks were the most consistent landscape barrier across species (present in the top-3 resistance predictors for 7 of 8 species), while riparian corridors were the most consistent facilitator of gene flow (significant positive partial Mantel correlation in 6 of 8 species). Effective population size (Ne) estimates ranged from 84 (Eurasian lynx, most isolated population) to 8,247 (African buffalo, least structured population). Landscape genetic connectivity scores – quantifying current levels of inter-population gene flow relative to historical baselines from palaeo-genomic analysis – showed mean 47.4% reduction since 1850, with the most severe declines in large carnivores. Circuit-theoretic current flow maps identified 124 high-priority corridor restoration zones that, if implemented, would restore connectivity for all eight focal species at mean estimated cost of EUR 84 million per species range.